1994
DOI: 10.2307/1591839
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Epithelial Cell Monolayers by Turkey Strains of Pasteurella multocida

Abstract: Two serotype 3,4:A strains of Pasteurella multocida that differ in virulence in turkeys were examined for their ability to invade epithelial cell monolayers grown in tissue culture. Both organisms were comparably adherent to cells of turkey kidney origin. However, the virulent strain (86-1913) penetrated primary turkey kidney epithelial cell monolayers at 10 times the level of the low-virulence vaccine strain. The virulent strain was also able to invade porcine epithelial cells (PK15) and feline epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The effect was due to haemagglutinins associated with the capsule and not to hyaluronic acid. The significance of this for the pathogenesis of fowl cholera is difficult to evaluate as it is known that strains of P. multocida show low levels of adhesion in vitro (Lee et al, 1994;Rhoades & Rimler, 1990a). Encapsulation of toxigenic serovar D isolates from swine was shown not to improve adhesion to porcine respiratory tract cells and mucus when compared with uncapsulated variants (Jacques et al, 1993).…”
Section: Capsule and Somatic Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was due to haemagglutinins associated with the capsule and not to hyaluronic acid. The significance of this for the pathogenesis of fowl cholera is difficult to evaluate as it is known that strains of P. multocida show low levels of adhesion in vitro (Lee et al, 1994;Rhoades & Rimler, 1990a). Encapsulation of toxigenic serovar D isolates from swine was shown not to improve adhesion to porcine respiratory tract cells and mucus when compared with uncapsulated variants (Jacques et al, 1993).…”
Section: Capsule and Somatic Antigensmentioning
confidence: 99%
“…The relevance of these models for neuraminidase in fowl cholera seems uncertain. Since avian respiratory epithelial cells contain neuraminic acid residues (Castells et al, 1990), it has been speculated that neuraminidase could, by degeneration of the acid, expose other carbohydrate residues which could act as receptors for strains of P. multocida, thereby facilitating invasion (Lee et al, 1994). Recently, it was shown that mice passively immunized with rabbit antiserum to neuraminidase from P. multocida A:3 were protected against subsequent homologous challenge infection (Ifeanyi & Bailie, 1992).…”
Section: Neuraminidasementioning
confidence: 99%
“…In turkeys, the lymphoid tissue is localized on the lower-eyelid conjunctiva and fully develops by three weeks of age. The conjunctiva-associated lymphoid tissue resembles, in many aspects, the mucosa-associated lymphoid tissues of the Pasteurella multocida adhesion to epithelial cells has received some interest (29,30,31,67,75). Studies of the HeLa cell model revealed that the capsular hyaluronic acid of serogroup A;3,4 strains off.…”
Section: Intestinal Tract In General the Potential Of Infection Thromentioning
confidence: 99%
“…multocida promotes bacterial adhesion (30). Electron microscopy studies of cultured turkey kidney epithelial cells indicated that P. multocida associates with cilia, and that internalization occurs on thickened protrusions of the epithelial cell surface (75). Although the author demonstrated that internalized bacteria were not associated or enclosed in cytoplasmic organelles, the author did not examine whether or not intracellular bacteria were resistant to Many animal species exhibit age-related changes of mucosal epithelial cell surface glycoproteins.…”
Section: Intestinal Tract In General the Potential Of Infection Thromentioning
confidence: 99%
See 1 more Smart Citation